Fabrication of core-shell sol-gel hybrid molecularly imprinted polymer based on metal–organic framework. (December 2019) - Wei, Ze-Hui; Zhang, Rong-Rong; Mu, Li-Na; Huang, Yan-Ping; Liu, Zhao-Sheng
Graphical abstract: Highlights: A core-shell organic-inorganic hybrid MIPs was conveniently synthesized. Metal-organic frameworks 177 was firstly used to prepare MIPs. The obtained MIPs have high adsorption capacity and imprinting effect. The faster binding kinetics and transfer-mass speed were achieved. Abstract: A core-shell organic-inorganic hybrid molecularly imprinted polymer (MIP) based on metal-organic framework 177 (MOF-177) was designed and synthesized. In the polymerization system, S -amlodipine ( S -AML) was used as template, methacrylic acid as functional monomer, tetraethoxysilane as crosslinker, MOF-177 as core support material and acetic acid as catalyst. The influences of the ratio of S -AML to methacrylic acid, the content of the crosslinker, the concentration of the catalyst, polymerization time as well as ultrasonic process on the affinity of the MOF-177@MIPs were investigated. The experiments of static adsorption equilibrium demonstrated that the MOF-177@MIPs had higher adsorption capacity ( Q max  = 1.31 mmol g −1 ) than that of the non-imprinted polymers (MOF-177@NIPs, Q max  = 0.23 mmol g −1 ) with maximum imprinting factor (IF) of 5.79. The faster binding kinetics and transfer-mass speed were obtained on the MOF-177@MIPs than on traditional non-core-shell MIPs. These studies suggested that using MOF-177 as core to prepare MIPs is a powerful approach to core-shell organic-inorganic hybrid MIPs with higher affinity and selectivity.